MENINGKATKAN PROSES DAN HASIL BELAJAR MATEMATIKA DENGAN PENDEKATAN PEMBELAJARAN KOGNITIF PADA SISWA SD PONDOK RANGGON 02 JAKARTA TIMUR - Siti Rohmi Yuliati (Fakultas Ilmu Pendidikan Universitas Negeri Jakarta, 2006)
Many students find difficult and uninteresting to learn mathematics. On the other hand, many teachers find problems in teaching certain concepts in mathematics. Consequently the learning achievement in mathematics in all grades is almost unsatisfactory. This classroom action research found an instructional model to overcome some problems faced by the students of the second grade at Pondok Rangon Primary School 02, East Jakarta. Applying this classroom action research in one cycle with two reflections, the teacher can improve the students’ learning achievement. This research suggests to do more modification of the instructional model in the following cycle to obtain better result.